Euro area SMEs under financial constraints: Belief or reality? - Concha Artola; Veronique Genre (Center for Economic Studies and ifo Institute (CESifo), 2011)
During the recent financial crisis, euro area firms, and especially Small and Medium-sized Enterprises, have been reporting acute problems of access to external finance. Using firm-level replies to the SME survey on access to finance, we use two indicators of financing constraints based on perceptions on the one side and on experienced financing constraints on the other and run probit and multinomial regressions model to determine which firms', sectoral or national characteristics drove perceptions and experienced financial constraints during the recent financial turmoil. We find that perceptions of financing crunch was broadly based across firms but those firms who really experienced a credit crunch tended to be small and young, confirming the fact that SMEs tend to suffer more when credit standards are tightened.
Keywords: E22; G30; L11; O16; 330; financial crisis; financing constraints; credit rationing; small and medium-sized enterprises; survey data